The Influence of Digital Pocket Book Learning Media on the Knowledge and Attitudes of Students of SMAN 5 Samarinda Regarding Sexually Transmitted Infections - rahmah, fitria; Toruan, Vera Madonna Lumban; Yudia, Riries Choiru Pramulia (Jurnal Ilmu Kesehatan, 2024)
There are more than thirty different types of germs known to be transmitted through sexual contact. This research aims to determine the effect of health education through digital pocket book learning media on the knowledge and attitudes of students at SMAN 5 Samarinda towards sexually transmitted infections, using a quasi-experiment with the accidental sampling method. Respondents, selected from a total of 1068 students, numbered 92 students aged 14 to 16 years during a one-week analysis of the benefits and positive impact of digital pocket book media intervention on students knowledge and attitudes. Data analysis used validity and reliability tests on the pre-test and post-test questionnaires, followed by paired T-tests and Wilcoxon tests on the results of the influence of the digital pocket book intervention. All sexually transmitted infection questionnaires were made reliable and valid for respondents to understand. The results of the paired T-test on students knowledge showed an average increase in knowledge scores of 9.47%, with a difference in the increase in knowledge results ranging between 3.2% and 15.2% among respondents. Regarding attitudes, students obtained an average increase in positive attitude scores of 8.17%, with a difference in the increase in positive attitude results ranging from 5.4% to 11.9% among respondents. The results of the Wilcoxon test on student knowledge showed a positive influence on all respondents, with an average knowledge value resulting from the intervention amounting to 93%. Similarly, students attitudes were positively influenced by all respondents, with an average attitude value resulting from the intervention of 92%.